2015
DOI: 10.1159/000438582
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine Exposure Impairs Myocardial Resistance to Ischaemia Reperfusion and Oxidative Stress

Abstract: Background/Aims: Hyperhomocysteinaemia is recognised as a strong independent risk factor for developing cardiovascular disease. This study investigated how an acute homocysteine dose affected cardiac performance during ischaemia reperfusion and cardiomyocyte contractility and morphology under normal conditions and during oxidative stress. Methods: Cardiac function was measured in isolated and perfused rat hearts before and after 40 minutes' global normothermic ischaemia. Where used, 0.1 mM L-homocysteine was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Accumulated studies have indicated that Hcy as an intermediate metabolite of cysteine and methionine can cause endothelial dysfunction (Zhang et al, 2017 ). For instance, patients with hyperhomocysteinemia usually show decreased numbers of endothelial cells with impaired endothelial activities in endothelial proliferation, migration and adhesion, which all do harm to human heart health (Jamaluddin et al, 2007 ; Almashhadany et al, 2015 ). Experimentally, Hcy has been proved to be associated with disturbed cardiac substrate metabolism, mitochondrial dysfunction and adverse cardiac remodeling with increased myocardial stiffness (Joseph et al, 2003 ; Devi et al, 2006 ; Suematsu et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulated studies have indicated that Hcy as an intermediate metabolite of cysteine and methionine can cause endothelial dysfunction (Zhang et al, 2017 ). For instance, patients with hyperhomocysteinemia usually show decreased numbers of endothelial cells with impaired endothelial activities in endothelial proliferation, migration and adhesion, which all do harm to human heart health (Jamaluddin et al, 2007 ; Almashhadany et al, 2015 ). Experimentally, Hcy has been proved to be associated with disturbed cardiac substrate metabolism, mitochondrial dysfunction and adverse cardiac remodeling with increased myocardial stiffness (Joseph et al, 2003 ; Devi et al, 2006 ; Suematsu et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Homocysteine (Hcy) is an intermediate metabolite of cysteine and methionine. Large numbers of evidences have confirmed that elevated plasma levels of Hcy as an independent risk factor may induce endothelial dysfunction through oxidative stress and apoptosis, and eventually lead to the occurrence and development of human CVD (Almashhadany et al, 2015 ; Baggott and Tamura, 2015 ). However, Hcy-mediated toxicity toward cardiomyocytes was not well demonstrated, and the underlying mechanism remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…[ 29 ] Moreover, HHcy was shown to lead to dysfunction and apoptosis of cardiomyocytes, an effect that was mediated via other signaling pathways, such as activation p38 MAPK. [ 30 , 31 ] Therefore, current evidence suggests that HHcy may aggravate CAD via its interaction with both the endothelial cells and cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfur amino acids such as homocysteine, methionine, SAM, SAH, and cysteine are involved in various essential metabolic pathways, including GSH synthesis and protein synthesis, and transmethylation reactions. Although homocysteine contributes to GSH synthesis ( 51 ), various studies have demonstrated that hyperhomocysteinemia ultimately induces oxidative stress and apoptosis ( 52 , 53 ). Betaine treatment can directly influence homocysteine concentrations via stimulating homocysteine to form methionine to regulate SAA concentrations.…”
Section: Anti-inflammatory Effects Of Betaine On Diseasesmentioning
confidence: 99%